Refining the chronostratigraphy of the Karoo Basin, South Africa: Magnetostratigraphic constraints support an early Permian age for the Ecca Group - Belica, M.; Tohver, E.; Poyatos-Moré, M.; Flint, S.; Parra-Avila, L.; Lanci, L.; Denyszyn, S.; Pisarevskiy, Sergei (Blackwell Publishing Ltd, 2017)
© The Authors 2017. The Beaufort Group of the Karoo Basin, South Africa provides an important chrono- and biostratigraphic record of vertebrate turnovers that have been attributed to the end-Permian mass extinction events at ca. 252 and 260 Ma. However, an unresolved controversy exists over the age of the Beaufort Group due to a large data set of published U-Pb SHRIMP (Sensitive High Resolution Ion Microprobe) zircon results that indicate a ca. 274-250 Ma age range for deposition of the underlying Ecca Group. This age range requires the application of a highly diachronous sedimentation model to the Karoo Basin stratigraphy and is not supported by published palaeontologic and palynologic data. This study tested the strength of these U- Pb isotopic data sets using a magnetostratigraphic approach. Here, we present a composite ~1500 m section through a large part of the Ecca Group from the Tanqua depocentre, located in the southwestern segment of the Karoo Basin. After the removal of two normal polarity overprints, a likely primary magnetic signal was isolated at temperatures above 450 °C. This section is restricted to a reverse polarity, indicating that it formed during the Kiaman Reverse Superchron (ca. 318-265 Ma), a distinctive magnetostratigraphic marker for early-middle Permian rocks. The Ecca Group has a corresponding palaeomagnetic pole at 40.8°S, 77.4°E (A95= 5.5°). U-Pb SHRIMP ages on zircons are presented here for comparison with prior isotopic studies of the Ecca Group. A weighted mean U-Pb age of 269.5 ± 1.2 Ma was determined from a volcanic ash bed located in the uppermost Tierberg Formation sampled from the O + R1 research core. The age is interpreted here as a minimum constraint due to a proposed Pb-loss event that has likely influenced a number of published results. A comparison with the Geomagnetic Polarity Time Scale as well as published U-Pb TIMS ages from the overlying Beaufort Group supports a ca. 290-265 Ma age for deposition of the Ecca Group.